Design and Build 2D Android-based Adventure Game “Excuse Me” - Muhammad Nur Kholis; Cindy Taurusta; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
Manners are a must for a child as basic education from an early age. Learning manners should be taught in childhood starting with an introduction to simple manners and manners. This encourages the idea to create a game that can be used as a tool in teaching etiquette for early childhood. Learning methods accompanied by play will make it easier for children to understand things easily. This educational game is entitled